Production and Profitability of Maize as Influenced by Different Levels of Nitrogen, Phosphorus and Zinc in Central Plateau Zone of Maharashtra - Keteku, A. K.; Narkhede, W. N.; Khazi, G. S. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was carried out on clayey soil at the experimental farm, AICRP on integrated farming systems, VNMKV, Parbhani during kharif 2014 to evaluate the effect of nitrogen, phosphorus and zinc on yield attributes, yield and economics of maize crop. The experiment was laid out in split plot design comprising two main plot factors (N and Zn) and P as Sub-plot factors. Nitrogen was applied at three levels (100, 125 and 150 kg ha-1), Zinc was applied at two levels (25 and 35 kg ZnSO4 kg ha-1) and phosphorus was applied at three levels (50, 75 and 100 kg ha-1). Application of nitrogen at 150 kg and 125 kg ha-1 was found at par for maize grain yield and were significantly superior over 100 kg N ha-1. The application of 25 and 35 kg ZnSO4 ha-1 did not affect maize grain yield significantly. Similarly, application of 100 and 75 kg P ha-1 were at par in respect to grain yield and was significantly superior over 50 kg P ha-1. Gross monetary returns, net monetary returns and B:C ratio increased with increasing level of N, P and Z except in B:C ratio where 75 kg P ha-1 recorded maximum value (2.83). A significant N×P interaction was observed in respect to no. grains cob-1 and grain weight plant-1. The interaction effect between nitrogen and zinc was also significant on maize spindle yield.